2005
DOI: 10.1093/fampra/cmi092
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of using different methods to assess cardiovascular risk in primary care

Abstract: Our results suggest important clinical and economic consequences when comparing European guidelines or ATPIII guidelines for the treatment of dyslipidemic patients in general practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 13 publications
3
16
0
2
Order By: Relevance
“…In our study, risk estimates with the three equations were different, similar to the findings from previous studies using different risk algorithms [6,[27][28][29]. The high risk group was largest (25.4%) when risk estimation was done with NCEP-ATP III criteria, and smallest (8.2%) when the risk was estimated using WHO/ISH criteria.…”
Section: Papersupporting
confidence: 84%
See 2 more Smart Citations
“…In our study, risk estimates with the three equations were different, similar to the findings from previous studies using different risk algorithms [6,[27][28][29]. The high risk group was largest (25.4%) when risk estimation was done with NCEP-ATP III criteria, and smallest (8.2%) when the risk was estimated using WHO/ISH criteria.…”
Section: Papersupporting
confidence: 84%
“…We studied the CHD risk (NCEP-ATP III), the total CVD risk (WHO/ISH), and the risk of CVD mortality (SCORE). Finally, some previous studies have been confined to those with selected risk factors [28,29], whereas others had excluded participants with certain risk factors. We did not select participants according to the presence or absence of risk factors, and therefore our data may be more applicable to the community at large.…”
Section: Malementioning
confidence: 99%
See 1 more Smart Citation
“…In Spain, some authors reported a prevalence of high risk in asymptomatic and non-diabetic individuals ranging from 4.1-9.2% (Gonzalez et al 2006;Buitrago et al 2007;Fornasini et al 2006). In one of the studies, the prevalence of high-risk individuals raises to 29.2% when diabetic patients were included (Fornasini et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Uncritical adoption of such protocols may result in negative clinical and economic consequences. 43 To address the absence of a CVD risk profiling tool for developing countries, WHO in 2000 developed a package for the assessment and management of cardiovascular risk in low-resource settings. 44 The package, developed through consultations with experts from all WHO regions, was designed as an adaptable, cost-effective tool for systematic case management at all health-care levels, and consequently for scaling up countries' health systems.…”
mentioning
confidence: 99%